Pengunaan Buku Teks Sejarah Indonesia Pada Satuan Pendidikan Menengah atas Dalam Kurikulum 2013 - Anju Nofarof Hasudungan (Education & Learning, 2021)
This study aims to describe the implementation of the Indonesian history textbook used in the 2013 curriculum at SMAN 1 Rupat, Riau Province. Indonesian history textbooks are still the main source of learning in the learning process. The Ministry of Education and Culture of the Republic of Indonesia has provided Indonesian history textbooks in the 2013 curriculum. Therefore, it is interesting to look at the characteristics of the 2013 curriculum itself. This is closely related to the background and objectives of implementing the 2013 curriculum and books as a support tool for the curriculum. The research method used is library research which is research based on searching the literature related to the issues to be discussed. The data in this library research is obtained through extracting and tracing Indonesian history textbooks, journals, and internet sites with reliable sources. The results show that the use of Indonesian history textbooks at SMAN 1 Rupat is in accordance with the background of the 2013 curriculum implementation objectives. In the future, it is necessary to study the use of Indonesian history textbooks in the current Merdeka Belajar concept.